2017
DOI: 10.1038/s41598-017-03315-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a stable laboratory co-culture of acidophilic nanoorganisms

Abstract: This study describes the laboratory cultivation of ARMAN (Archaeal Richmond Mine Acidophilic Nanoorganisms). After 2.5 years of successive transfers in an anoxic medium containing ferric sulfate as an electron acceptor, a consortium was attained that is comprised of two members of the order Thermoplasmatales, a member of a proposed ARMAN group, as well as a fungus. The 16S rRNA identity of one archaeon is only 91.6% compared to the most closely related isolate Thermogymnomonas acidicola. Hence, this organism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 42 publications
5
78
0
Order By: Relevance
“…Using CARD-FISH and 16S-rRNA analysis, we found that fluidic cultivation was successful. Indeed this technique enabled the cultivation of the first co-culture that contained only an ARMAN species along with a single helper organism (Figure 4 d), dubbed as B_DKE that we had previously observed in the more complex co-culture obtained by conventional cultivation techniques 30 . Most likely, B_DKE is necessary as producer for compounds that cannot be produced by the multi-auxotrophic ARMAN organism.…”
Section: Enrichment Of Rare Microbial Speciesmentioning
confidence: 91%
See 1 more Smart Citation
“…Using CARD-FISH and 16S-rRNA analysis, we found that fluidic cultivation was successful. Indeed this technique enabled the cultivation of the first co-culture that contained only an ARMAN species along with a single helper organism (Figure 4 d), dubbed as B_DKE that we had previously observed in the more complex co-culture obtained by conventional cultivation techniques 30 . Most likely, B_DKE is necessary as producer for compounds that cannot be produced by the multi-auxotrophic ARMAN organism.…”
Section: Enrichment Of Rare Microbial Speciesmentioning
confidence: 91%
“…Therefore, fluidic cultivation of a stable laboratory culture of anaerobic acidophilic nanoorganisms 30 was conducted. This ARMAN co-culture was derived from the aforementioned acidophilic environmental AMD biofilm (shown in Figure 4 a) and evolution by several transfers in anoxic medium under planktonic conditions led to a community that was composed of three novel archaea including an ARMAN species and a fungus 30 (Figure 4 c). We used this co-culture as inoculum for microfluidic cultivation inside the anoxic gasket.…”
Section: Enrichment Of Rare Microbial Speciesmentioning
confidence: 99%
“…Metagenome-assembled genomes (MAGs) on the other hand rarely contain full-length 16S rRNA genes [44,45]. While there are notable exceptions to this rule [46,47], the above assignment strategies are generally not expected to work well for today's SAGs and MAGs.…”
Section: Gene Homology-based Assignmentsmentioning
confidence: 99%
“…S1. (167,168,171,174) amino acids (71, 110-117, 120-128, 130-141, 144-166, 175-178) G1P (precursor for activated sugars) (42)(43)(44)(45)(46)(47)(48)(49)(50) activated sugars (185-209, 97, 215) glycogen (193,185,214) molecular building blocks via acetyl-CoA (36-39) IPP (87-91), pyruvate (41), DHAP (42)(43)(44)(45)(46)(47) AdoCbl (179-184) NAD(P)H (10)(11)(12)(13)(14)(15)(16), FADH 2 (3)(4)(5)(6)(7)(8)(9) PLP (1) THF derivate (17,18,(20)(21)(22)(23)(24)(25) red. ferredoxin (18,216) NTPs (51-69, 71-77, 80, 82) dNTPs (69, 70, 77, 79, 81, 82) ATP GTP (83,220) energy demanding processes synthesis of activated sugar glycogen degrataion (210), synthesis of activated sugars (186, 192-194, 196, 198, 203, 205, 207, 215), transfer of glycosyl gropus (229) lipid biosynthesis…”
Section: Huberiarchaeum Crystelensementioning
confidence: 99%
“…These results provide insight into host-symbiont interactions among members of two uncultivated archaeal phyla that thrive in a deep subsurface aquifer.The DPANN (Diapherotrites, Parvarchaeota, Aigarchaeota, Nanoarchaeota, Nanohaloarchaeota) [1] radiation is a proposed monophyletic group of diverse archaeal phyla whose organisms exhibit mainly reduced genomes with limited metabolic capacities [2]. While most of these archaea were suggested to live in symbiosis with other microorganisms, respective hosts were only described for Nanoarchaeota [3,4] and Micrarchaeota (ARMAN) symbionts [5][6][7]. However, no DPANN-host interaction has been described for representatives in aquifer systems, where these archaea are particularly abundant and very diverse [2].Recently, subsurface fluids discharged by a cold, CO2-driven geyser at the Colorado Plateau, Utah (Crystal Geyser) revealed the presence of multiple novel archaeal organisms,…”
mentioning
confidence: 99%